Optimization of National Zakat Management through the Effectiveness of the Role of Stakeholders of Zakat Management Organizations (International Journal of Scientific Research and Management (IJSRM), 2024)
This research shows that stakeholders are running the Zakat governance system effectively. There is a contradiction in the role between the regulatory and executive functions of the national zakat management institution. The research method used is descriptive qualitative, which compares ideal conditions with actual conditions through secondary data research, interviews, and group discussions. The data processed are in the form of zakat law documents, government regulations, BAZNAS regulations, zakat acquisition calculation index, data from the central statistics agency, minutes of discussion group forums and confirming interviews with sources of amil zakat, samples using the purposive sampling method by finding samples through snowball sampling techniques. The study results show that reforms need to be carried out immediately on the role of zakat governance stakeholders so that national zakat management is more optimal and effective and, in the end, can provide more comprehensive benefits for the community